Sympoietic growth: living and producing with fungi in times of ecological distress - Stöckelová, Tereza; Senft, Lukáš; Kolářová, Kateřina (Agriculture and human values, 2023)
Drawing upon ethnographic research on human living and producing with fungi, and Haraway's theorization of sympoiesis and the model ecosystems of mycorrhizae developed in current mycological research, we offer a concept of sympoietic growth. Sympoiesis is a concept that suggests a way of thinking about growth as a more-than-human process and provides an alternative political imaginary both to current forms of economic growth and to the idea of "degrowth." We explore human-fungi co-operation in forests, an urban park, and a shopping mall, on a miso production farm, and in a Catholic parish to provide insights into the logic and relationships involved in sympoietic growth in the field of agriculture and food production. We argue that this form of food provision has a sustainable, (re)generative potential not only in ecological and social but also economic terms. In conclusion, we highlight three patterns of sympoietic growth: the absence of any urge to "take (back) control" over the multispecies dynamic on the part of the humans; a non-instrumental passion for more-than-human life; and a combination of intellectual and manual labor as a form of attachment to the more-than-human world.
Keywords: Fungi; Sympoiesis; Model ecosystems; Mushroom foraging; Degrowth